The effectiveness of health education provision of animated video media in improving COVID-19 prevention behavior post-vaccination among students of Muhammadiyah Islamic Boarding School Karangasem Paciran Lamongan - Eni Sumarliyah; Ira Purnamasari; Ade Susanty; Pipit Festi Wiliyanarti; Firman Firman; Dede Nasrullah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Vaccination in the context of dealing with COVID-19 has been promoted. The increasing number of cases showed the lack of community compliance in preventing the transmission of COVID-19 after Vaccination. Intrapersonal factors, such as changes in individual behavior, were the main focus of breaking the chain of the spread of COVID-19. This study aimed to determine the effectiveness of providing health education with animated video media on improving COVID-19 prevention behavior after Vaccination among students at the Karangasem Islamic Boarding School Paciran of Lamongan. This study used pre-experimental with one group pre-test and post-test design. The population was Muhammadiyah Islamic boarding school students in Karangasem Paciran Lamongan, which amounted to 460 and took samples of 332 people using a non-probability purposive sampling technique. The research instrument used a questionnaire 30 items. The results of knowledge have increased from pre-test sufficient knowledge (60.84%), and post-test good knowledge (81.02%) using the Wilcoxon signed rank test p=0.000 (<0.05). The results of attitudes have increased from pre-test negative attitude (70.78%) and post-test positive attitude (76.81%) using the Chi-square test p=0.001 (<0.05). The results of practice have increased from pre-test sufficient practice (62.95%), and post-test good practice (77.71%) using the Wilcoxon signed rank test p=0.000 (<0.05). In conclusion, the video animation media of health education was proven to increase post-vaccination COVID-19 prevention behavior among students at the Karangasem Islamic Boarding School Paciran of Lamongan.